Thermal and Dynamic Properties of Woven Kenaf/Carbon Fibre Reinforced Epoxy Hybrid Composite - Aisyah, Humaira Alias; Paridah, Md Tahir; Sapuan, Salit Mohd; Khalina, Abdan; Berkalp, Omer Berk; Lee, Seng Hua; Ramli, Natasha (MDPI AG, 2019)
The effects of carbon fiber hybridisation on the thermal properties of woven kenaf reinforced epoxy composites kenaf fibre were studied. Woven kenaf hybrid composites at the different weave designs of plain and satin, and fabric count of 5 × 5 and 6 × 6 were manually prepared by vacuum infusion technique.  Thermal properties of pure carbon fibre and hybrid composites were conducted by using thermogravimetric analyser (TGA) and differential scanning calorimeter (DSC). It was found that at high kenaf fibre content showed better thermal stability while the highest thermally stable was found in pure carbon fibre composite.  The TG and DTG results showed that the amount of residue decreased in plain-designed hybrid composite compared to satin-designed hybrid composite. The DSC data revealed that the presence of woven kenaf increase decomposition temperature.
Keywords: general_materials_science